Impacts of Urbanization on Stream Fish Assemblages: The Role of the Species Pool and the Local Environment - Czeglédi, István; Kern, Bernadett; Tóth, Rita; Seress, Gábor; Erős, Tibor (Frontiers in Ecology and Evolution, 2020)
Disentangling the mechanisms that determine community assembly in urban environments is a prerequisite for understanding the impacts of urbanization on the biota and for developing more effective rehabilitation strategies. Community structure in urban stream ecosystems is the sum of multiple processes, including local environmental and catchment level effects. However, the degree to which dispersal from the regional species pool influences urban stream communities still has not been rigorously examined. We studied the importance of the degree of urbanization, the local stream environment and the regional species pool on the assembly of stream fishes in the Pannon Biogeographic Region, Hungary. Correlation analyses between urbanization variables (human population size and a recently developed urbanization index) and local stream and riparian environmental variables did not show significant relationships, indicating that the examined 29 streams reacted to the degree of urbanization in a strongly individual manner. Variance partitioning in both linear regression and redundancy analyses showed that the downstream species pool was the most important determinant of fish species richness, community composition and abundance at urban stream sites. The effect of the local stream environment proved to be moderate, while purely urbanization variables explained only a very small proportion of variance in the data. The relative importance of shared fractions depended on the examined fish assemblage variable, but, in general, was also low or moderate. Additional principal component analyses indicated that community similarity between urban and associated non-urban “reference sites” varied widely, and that the sites did not separate to urban and reference fish community types. Overall, the results highlight that the degree of urbanization is not a strong determinant of local stream habitat and fish community characteristics in this region. Rather, historical species pool and stream characteristics shape fish communities with urbanization playing a rather individual role in some streams. Thus, rehabilitation of urban streams should not only focus on local habitat improvements, but rather consider how dispersal mechanisms from non- urban segments influence community organization at the urban sites.